SYNERGISTIC EFFECTS OF COMBINED THERAPY: ELECTROSTIMULATION WITH INFRARED LIGHT AND ULTRASOUND FOR CELLULITE - Šniepienė, Gražina; Urbonienė, Simona; Kasperavičiūtė, Simona (PROFESSIONAL STUDIES: Theory And Practice, 2022)
Cellulite, the problem of dimpled appearance of the skin that is present in 80-90 % of post-pubertal women and considerably affects quality of life. A wide range of products and treatments for cellulite reduction is available, however, there is is a lack of research what is effect of electrostimuliation with infrared and ultrasound on cellulite effected skin. Key words: elektrostimulation, infrared, ultrasound, stage III cellulite.